Effects of Flammulina velutipes mushroom residues on growth performance, apparent digestibility, serum biochemical indicators, rumen fermentation and microbial of Guizhou black goat - Yong Long; Yong Long; Yong Long; Yong Long; Wen Xiao; Wen Xiao; Yanpin Zhao; Yanpin Zhao; Chao Yuan; Defeng Wang; Yang Yang; Chaozhi Su; et al. (Frontiers in Microbiology, 2024)
IntroductionThe primary objective of the current study was to evaluate the effects of Flammulina velutipes mushroom residue (FVMR) in a fermented total mixed ration (FTMR) diet on the fattening effect and rumen microorganisms in Guizhou black male goats.MethodsA total of 22 Guizhou black male goats were allocated into two groups using the Randomized Complete Block Design (RCBD) experimental design. The average initial weight was 22.41 ± 0.90 kg and with 11 goats in each group. The control group (group I) was fed the traditional fermentation total mixed ration (FTMR) diet without FVMR. Group II was fed the 30% FVMR in the FTMR diet.ResultsThe results showed that compared with group I, the addition of FVMR in the goat diet could reduce the feed cost and feed conversion ratio (FCR) of group II (p < 0.01). Notably, the apparent digestibility of crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF), and dry matter (DM) were higher in group II (p < 0.01). The levels of growth hormone (GH), immunoglobulin A (IgA), and immunoglobulin M (IgM) in group II were higher than that of group I (p < 0.01), which the level of glutamic oxalacetic transaminase (ALT) and interleukin-6 (IL-6) was noticeably lower than that of group I (p < 0.01). 30% FVMR in FTMR diets had no effect on rumen fermentation parameters and microbial composition at the phylum level of Guizhou black male goats (p > 0.05). However, at the genus level, the relative abundance of bacteroidal_bs11_gut_group, Christensenellaceae_R-7_group and Desulfovibrio in group II was lower than in group I (p < 0.05), and the relative abundance of Lachnospiraceae_ND3007_group was higher than in group I (p < 0.01).DiscussionIn conclusion, the results of the current study indicated that 30% FVMR in the FTMR diet improves rumen fermentation and rumen microbial composition in Guizhou black male goats, which improves growth performance, apparent digestibility, and immunity.